Isotopic Characterization of Water Masses in the Southeast Pacific Region: Paleoceanographic Implications. Issue 1 (20th January 2022) - Reyes‐Macaya, Dharma; Hoogakker, Babette; Martínez‐Méndez, Gema; Llanillo, Pedro J.; Grasse, Patricia; Mohtadi, Mahyar; Mix, Alan; Leng, Melanie J.; Struck, Ulrich; McCorkle, Daniel C.; Troncoso, Macarena; Gayo, Eugenia M.; et al.
Abstract: In this study, we used stable isotopes of oxygen (δ 18 O), deuterium (δD), and dissolved inorganic carbon (δ 13 CDIC ) in combination with temperature, salinity, oxygen, and nutrient concentrations to characterize the coastal (71°–78°W) and an oceanic (82°–98°W) water masses (SAAW—Subantarctic Surface Water; STW—Subtropical Water; ESSW—Equatorial Subsurface water; AAIW—Antarctic Intermediate Water; PDW—Pacific Deep Water) of the Southeast Pacific (SEP). The results show that δ 18 O and δD can be used to differentiate between SAAW‐STW, SAAW‐ESSW, and ESSW‐AAIW. δ 13 CDIC signatures can be used to differentiate between STW‐ESSW (oceanic section), SAAW‐ESSW, ESSW‐AAIW, and AAIW‐PDW. Compared with the oceanic section, our new coastal section highlights differences in both the chemistry and geometry of water masses above 1, 000 m. Previous paleoceanographic studies using marine sediments from the SEP continental margin used the present‐day hydrological oceanic transect to compare against, as the coastal section was not sufficiently characterized. We suggest that our new results of the coastal section should be used for past characterizations of the SEP water masses that are usually based on continental margin sediment samples. Plain Language Summary: The Southeast Pacific (SEP) is a large marine region along the western continental margin of South America, where water masses that are transported from equatorial, subtropical, and subpolar latitudes converge. This study aims to understand the characteristics of water masses using isotopes of oxygen (δ 18 O), deuterium (δD), and dissolved inorganic carbon (δ 13 CDIC ) along with other parameters, such as temperature, salinity and oxygen, and nutrient concentrations. Significant differences in the chemical and isotope composition of SEP water masses are described. The distribution of the water masses above 1, 000 m differs between our new coastal (71°–78°W) and partly existing oceanic (82°–98°W) sections. This has implications for the interpretation of paleoceanographic records, which are typically collected from the continental margin rather close to the coast. Key Points: The first biogeochemical and spatial characterization of δ 18 O, δD, and δ 13 CDIC from coastal water masses in the Southeast Pacific (SEP) The upper 1, 000 m between the open ocean and coastal regions show strong differences in water mass chemistry and geometry Coastal data provide information that can aid in reconstructions of past ocean conditions in the SEP